2001
DOI: 10.1113/eph8602076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Progesterone on Coronary Blood Flow in Anaesthetized Pigs

Abstract: The present study was designed to investigate the effect of progesterone on the coronary circulation and to determine the mechanisms involved. In pigs anaesthetized with sodium pentobarbitone, changes in left circumflex or anterior descending coronary blood flow caused by intravenous infusion of progesterone at constant heart rate and arterial blood pressure were assessed using an electromagnetic flowmeter. In 14 pigs, infusion of 1 mg h−1 of progesterone caused an increase in coronary blood flow without affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…Previous reports in anesthetized pigs have shown that 17β-estradiol and progesterone cause vasodilatation through mechanisms which involve the endothelial release of nitric oxide [27, 33, 34]. The increase in the maternal peripheral serum levels of human placental lactogen which accompanies the spontaneous increases in maternal peripheral serum levels of estrogens and progesterone as pregnancy advances [see, for example, ref.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in anesthetized pigs have shown that 17β-estradiol and progesterone cause vasodilatation through mechanisms which involve the endothelial release of nitric oxide [27, 33, 34]. The increase in the maternal peripheral serum levels of human placental lactogen which accompanies the spontaneous increases in maternal peripheral serum levels of estrogens and progesterone as pregnancy advances [see, for example, ref.…”
Section: Discussionmentioning
confidence: 99%
“…The infusions were completed in 1 h by using an infusion pump (Model 22, Harvard Apparatus) working at constant rate of 1 ml/min. In a previous study on the effects of progesterone on the coronary circulation, it has been shown that this period of 1 h was required to attain steady state changes in coronary blood flow [1]. After the infusion was stopped, observations were continued for 1.5 h. The dose of progesterone used corresponded to the hourly amount of hormone which is reported to be produced by the corpus luteum during the mid-luteal phase of the ovarian cycle in women [11]and is reported to be analogous in pigs [12].…”
Section: Methodsmentioning
confidence: 99%
“…The present investigation was therefore designed, in a similar manner of that of Molinari et al [1], to quantify the effect of acute administration of progesterone on mesenteric, renal and iliac blood flow in anesthetized female pigs and to determine the mechanisms involved. For this purpose, experiments were performed during constant heart rate and arterial blood pressure to avoid interference by hemodynamic and reflex effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators suggested that progesterone in high concentration potentiate the GABA mediated baroreflex sympatho-inhibition within RVLM 9,10 . Again, some investigators have suggested that progesterone may cause vasodilatation by releasing NO from endothelium 18,19 .…”
Section: Resultsmentioning
confidence: 99%